Systemic adverse reactions to local anesthetics - Tijanić Miloš; Stojanović Simona; Burić Kristina; Todorović Kosta; Spasić Milan (Medicinski fakultet i Klinika za stomatologiju, Niš, 2019)
Introduction: Local anesthetics are the most commonly used drugs in everyday dental and medical and increasingly in cosmetic practice. Today there are a number of local anesthetics that are divided into two groups based on their structure: ester and amide local anesthetics. Although their use in everyday work is generally safe, there is a possibility of adverse reactions that may be psychogenic, toxic, immunologic and specific adverse reactions. The aim of this work is to highlight the mechanism of occurrence and symptoms of possible adverse reactions to local anesthetics. Conclusion: If you experience systemic adverse reactions to the local anesthetic, the biggest problem in clinical practice, is a recognition of the nature of adverse reactions and providing appropriate therapy in conjunction with the resulting reaction. Speed and security to identify adverse reactions to local anesthetic can be of vital importance for the patient.